Cultural-Based Diabetes Self-Care Management Education for People with Type 2 Diabetes Mellitus: Empowering Community Health Workers (Kaders) Program Evaluation - Kadar, Kusrini S.; Mulyana, Andi Saputri; Indargairi, Indargairi; Jeremiah, Rohan Dexter (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aim: The aim of this study was to understand the perspectives of Kaders, community health nurses (CHNs), and the community on an empowerment program for Kaders in Indonesia. The program aimed to help Kaders provide cultural-based diabetes self-care management education for people with type 2 diabetes mellitus (T2DM). Methods: The empowerment program consisted of a four-month training program, including two full-day sessions on cultural-based health education for people with T2DM, followed by four months of monitoring T2DM patients. Fifteen Kaders from community health centers in Makassar City participated in the program. Focus group discussions (FGDs) were conducted with Kaders to explore their perceptions and experiences related to the program. Interviews were also conducted with CHNs and people with T2DM regarding their perceptions of the program. Results: The FGDs with Kaders resulted in four themes: overall training, guideline book, education and monitoring program, and potential obstacles. CHNs highlighted the benefits of the program, the guideline book, and the impact on patients. Patients identified three themes, including the benefits of the program, what was taught, and what was improved. Conclusion: The empowerment program for Kaders in Indonesia has proven to be beneficial for Kaders, CHNs, and the community. Kaders have the potential to provide effective and efficient health education with proper preparation and empowerment through knowledge and skills.